2018
DOI: 10.22146/studipemudaugm.38010
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF SOCIAL MEDIA ON MIGRATION DECISION-MAKING PROCESSES: Case of Indonesian Student in University of Groningen

Abstract: Objective: This research aims to explain the impact of social media on the migration decisionmaking process of Indonesian student migrants in University of Groningen who used a social media account. In detail, this research will consider the role of social media in the migration decision-making process of students who emigrated from Indonesia and how they uses social media in the context of the migration decision-making process. Methods: The data collected included qualitative data from in-depth interviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…Despite having a mixed bag of how Africans are portrayed in Western media, Africans continue to make long journeys to the West. In a study carried out by Hidayati (2017), he reported that migrant international students base their decisions to migrate on "on benefit evaluation according to the cost and benefits of migrations. The cost may include to separate with parents and family, and also the problems in settling in new place and new society," (Hidayati, 2017, p. 522).…”
Section: The Power Of Foreign Media On Migrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite having a mixed bag of how Africans are portrayed in Western media, Africans continue to make long journeys to the West. In a study carried out by Hidayati (2017), he reported that migrant international students base their decisions to migrate on "on benefit evaluation according to the cost and benefits of migrations. The cost may include to separate with parents and family, and also the problems in settling in new place and new society," (Hidayati, 2017, p. 522).…”
Section: The Power Of Foreign Media On Migrationmentioning
confidence: 99%
“…The cost may include to separate with parents and family, and also the problems in settling in new place and new society," (Hidayati, 2017, p. 522). Hidayati (2017) reported that disparities in "demographic, social and economic circumstances " (p. 515) are compelling motivations for why people migrate. The migration network theory coined by Lee (1966) assumes that migrants who have contacts in their target nation are more likely to move to that nation, speaking to the social aspect of why migrants choose their destinations.…”
Section: The Power Of Foreign Media On Migrationmentioning
confidence: 99%
See 3 more Smart Citations